Retrieval and Storage of Research Information by the Post Graduate Students of Kerala Agricultural University (Indian Journal of Extension Education, 2015)
The retrieval and storage of research information is an important aspect when it comes to the post graduate students doing research. As far as agriculture students are considered, the research information retrieval is unavoidable for carrying out research works. Therefore, the study was conducted to find out the information retrieval behavior and storage of information by the research graduates in Kerala Agricultural University. A questionnaire was prepared and distributed among 30 post graduate students in various disciplines. The study revealed that more that more than 50 per cent of students retrieved information regularly. Seventy percentage of students accessed information to supplement their lecture notes. Fifty percentages of respondents utilized the library facilities more than once in a week. Internet was the source used to retrieve information by the respondents. Sixty percentage of respondents stored information occasionally and 76.6 per cent of respondents had the habit of taking prints for storing the information.